ANALYSIS OF STEAM TURBINE GENERATOR 1 PERFORMANCE AT POWER PLANT 2 UTILITIES OF PT PERTAMINA RU V BALIKPAPAN (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2022)
Electrical energy is the energy that is needed by everyone at this time. Especially in the RU V Balikpapan refinery, electrical energy is used as a support for refinery operations. Electrical energy is generated from generators powered by steam turbines. In order not to be disrupted by the ongoing refinery operations, research is needed on the performance of steam turbine generators. Research on the performance of Steam Turbine Generator was conducted at PT. Pertamina RU V Balikpapan, jl. Yos Sudarso No. 1 Balikpapan from September 2021 to January 2022. The values of this research-free variable are pressure steam inlet and temperature steam inlet. While the variables tied to this study are the enthalpy value of the steam inlet and the efficiency value obtained. And for the control variable of this study is the aperture of governor valve inlet steam. Based on the results of the first observations in December 2020, the efficiency value of Steam Turbine Generator 1 in the first week was 59.073%, the second week 53.692%, the third week 60.449%, the fourth week 61,509%. For the second observations in December 2021 the efficiency value obtained in the first week was 61.564%, the second week 65.074%, the third week 62.429%, the fourth week 60,850%. Varying efficiency values due to changes in electrical power generated. The power generated the closer to the Most Economic Rating value, the greater the efficiency value obtained.